Urgensi Akta Notaris Dalam Pengalihan Hak Atas Merek Melalui Hibah Sebagai Bentuk Kepastian Hukum - Anggun Mulia, Yen Yen; Elly Hernawati (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Trademark rights can be transferred in several ways, namely inheritance, gift, will, agreement and other reasons permitted by law. The transfer of rights to a trademark through a gift requires a deed and this is stipulated in article 1682 of the Civil Code which reads as follows: